Kimura disease, a rare Ethiopian case report - Yohannis Derbew Molla; Hirut Tesfahun Alemu; Kassa Berie Zegeye; Tiruzer Bekele; Amanuel Kassa Tadesse; Isak Omer Answar (Heliyon)
Introduction: Kimura disease is a chronic inflammatory disorder predominantly affecting the head and neck region. The etiology of Kimura disease remains unclear. The disease mainly affects young adult males of Asian descent, with a higher prevalence in East Asian countries. Clinical presentation: a 48-year-old Ethiopian woman presented with swelling in both her lower extremities, which gradually progressed to include her abdomen and the rest of her body. Additionally, she had pain in multiple joints in her upper and lower extremities, high-grade fever, loss of appetite, night sweats, and unexplained weight loss over the same duration. Physical examination revealed swelling around the eyes (periorbital puffiness), enlarged nodes in the axillary, and inguinal areas on both sides of the body, and pitting edema. Investigations showed pneumonia, elevated renal function tests and kimura disease. Unfortunately, the patient signed medical advice before completing her management. Conclusion: despite its rarity in Ethiopia, it is imperative to consider Kimura disease as a potential diagnosis when evaluating lymphadenopathy and renal derangement.